2004
DOI: 10.1097/00001756-200410250-00017
|View full text |Cite
|
Sign up to set email alerts
|

Lack of ATP-evoked GABA and glutamate release in the hippocampus of P2X7 receptor−/− mice

Abstract: In this study we revealed the participation of P2X(7) receptors in the modulation of electrical stimulation and ATP-evoked GABA and glutamate release from mouse hippocampal slices. Whereas the uptake of radioactivity was not changed, the electrical stimulation-induced release of both [(3)H]glutamate and [(3)H]GABA was decreased in the hippocampus of P2X(7) receptor-deficient mice. ATP (10 mM) elicited [(3)H]glutamate and [(3)H]GABA efflux in wild-type mice, which was inhibited by the non-selective P2 receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 25 publications
4
58
0
Order By: Relevance
“…In contrast, under pathological conditions such as during inflammation, ischemia, spreading depression, and trauma, when upregulation of these receptors, changes in extracellular cation composition, and increased extracellular ATP levels have been reported (Kraig and Nicholson, 1978;Harris and Symon, 1984;Nilsson et al, 1993;Le Feuvre et al, 2002;Guerra et al, 2003;Narcisse et al, 2005), the participation of P2X 7 R might be expected to exacerbate the extent of cell damage. Indeed, evidence for the participation of P2X 7 R in the regulation of extracellular transmitter levels was provided from studies showing that ATP-evoked glutamate efflux from neuronal and non-neuronal cells was greatly attenuated in P2X 7 R-null hippocampal slices (Papp et al, 2004) and from those showing that P2X 7 R antagonists greatly attenuated the extent of cell damage after acute spinal cord traumatic injury (Wang et al, 2004). Although our in vitro studies support the notion that P2X 7 R contributes sites for ATP release from spinal cord astrocytes under extremely low divalent cation conditions, this observation remains to be confirmed in different preparations, such as in brain slices of ischemic mice.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, under pathological conditions such as during inflammation, ischemia, spreading depression, and trauma, when upregulation of these receptors, changes in extracellular cation composition, and increased extracellular ATP levels have been reported (Kraig and Nicholson, 1978;Harris and Symon, 1984;Nilsson et al, 1993;Le Feuvre et al, 2002;Guerra et al, 2003;Narcisse et al, 2005), the participation of P2X 7 R might be expected to exacerbate the extent of cell damage. Indeed, evidence for the participation of P2X 7 R in the regulation of extracellular transmitter levels was provided from studies showing that ATP-evoked glutamate efflux from neuronal and non-neuronal cells was greatly attenuated in P2X 7 R-null hippocampal slices (Papp et al, 2004) and from those showing that P2X 7 R antagonists greatly attenuated the extent of cell damage after acute spinal cord traumatic injury (Wang et al, 2004). Although our in vitro studies support the notion that P2X 7 R contributes sites for ATP release from spinal cord astrocytes under extremely low divalent cation conditions, this observation remains to be confirmed in different preparations, such as in brain slices of ischemic mice.…”
Section: Discussionmentioning
confidence: 99%
“…1 H-MRS ex vivo GABA levels include all GABA compartments, including astrocytic (Papp et al 2004;Sperlagh et al 2002) and other non-vesicular stores IC, ventral MGB (vMGB), and dorsal MGB (dMGB) were carefully selected separately in each rat. B: combined values of left and right hemispheres were shown in average group data.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of P2RX7 knockout mice have demonstrated that the receptor mediates ATP-induced ã-aminobutyric acid and glutamate transmission in the hippocampus. 39 P2RX7 may have a role to play in antidepressant action and susceptibility to mood disorders via its influence on hippocampal neurotransmission, 40 neuroprotection 41 or neuroinflammatory responses. 42 …”
Section: Discussionmentioning
confidence: 99%